Radiante conexión Coperari : lámpara generadora de señales para espacios de coworking (2018)
The objective of this document is to show the process and development of the Radiant Connection project: Coperari. Created from happiness as a starting point and inspiration, seeking to recreate an object that stimulates this emotion in people. This, taking into account external stimuli and internal changes of the body, taking as important blocks happiness from the personal point and studies carried out by experts in positive psychology, coupled with the connection of the positive changes brought by the light to this state of mind.